2018
DOI: 10.1039/c7cp08149a
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of gas phase copper(ii) acetylacetonate with slow electrons

Abstract: Understanding the fundamental processes underlying the interaction of organometallic compounds with low energy electrons is desirable for optimizing methodologies for nanoscale applications. In this work, we couple experimental measurements with theories to investigate the interaction of gas phase copper(ii) acetylacetonate, Cu(acac), with low energy (<12 eV) electrons. Near 0 eV, a multipole-bound anion is likely to act as the doorway for the formation of a transitory molecular anion which then undergoes stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 59 publications
(74 reference statements)
4
27
1
Order By: Relevance
“…The present results follow the same trend as those obtained for the Cu(acac) 2 system, for which the reaction Cu(acac) 2 * − → Cu(acac) + [acac] − is endothermic but by ∼1.5 eV. 38 Since, for the copper system, the [acac] − anion formed near 0 eV represents only 2.8% of the [Cu(acac) 2 ] − anion, we suggested that the fragmentation is favored by the accumulated energy via thermal excitation of some accessible vibration modes. In the present case, the yield of the [acac] − anion is ∼10 times larger than that of the Mn(acac) 2 − anion, and the energy threshold is also higher; therefore, the argument employed for the copper acetylacetonate system is unlikely.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The present results follow the same trend as those obtained for the Cu(acac) 2 system, for which the reaction Cu(acac) 2 * − → Cu(acac) + [acac] − is endothermic but by ∼1.5 eV. 38 Since, for the copper system, the [acac] − anion formed near 0 eV represents only 2.8% of the [Cu(acac) 2 ] − anion, we suggested that the fragmentation is favored by the accumulated energy via thermal excitation of some accessible vibration modes. In the present case, the yield of the [acac] − anion is ∼10 times larger than that of the Mn(acac) 2 − anion, and the energy threshold is also higher; therefore, the argument employed for the copper acetylacetonate system is unlikely.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…From these results and as shown by the energetic diagram (Figure 2b), the calculated electron affinity value of the acac radical from the Mn(II)(acac) (in the septet configuration, S = 3) + [acac] − agrees with the previously calculated value from Cu(acac) 2 . 38 In this S = 3 electronic configuration, the dissociative electron attachment to the Mn(acac) 2 molecule to form the [acac] − anion is found to be endothermic by 2.01 eV (Table 1). The fragmentation channel associated with the Mn(II)(acac) in the quintet electronic arrangement is found to be higher by 0.8 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The only conceivable additional reaction pathway is electron attachment into an empty d-orbital of Cu 2+ , thus leading to formal reduction to Cu(I). This changes the preferred coordination geometry 42 and is expected to also destabilize the binding of the oxalate linkers.…”
Section: Discussionmentioning
confidence: 99%